SEARCH OF COMPUTERS FOR DISCOVERY OF ELECTRONIC EVIDENCE - Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
In order to address the specific nature of criminal activities committed using computer networks and systems, the efforts of states to adapt or complement the existing criminal law with purposeful provisions is understandable. To create an appropriate legal framework for supressing cybercrime, except the rules of substantive criminal law predict certain behavior as criminal offenses against the confidentiality, integrity and availability of computer data, computer systems and networks, it is essential that the provisions of the criminal procedure law contain adequate powers of competent authorities for detecting sources of illegal activities, or the collection of data on the committed criminal offense and offender, which can be used as evidence in criminal proceedings, taking into account the specificities of cyber crime and the environment within which the illegal activity is undertaken. Accordingly, the provisions of the criminal procedural law should be designed to be able to overcome certain challenges in discovering and proving high technology crime, and the provisions governing search of computer for discovery of electronic evidence is of special importance.